CORPORATE EXCELLENCE IN NIGERIAN MANUFACTURING: A GUIDE TO FINANCIAL MASTERY - Yenagoa, Michael Ebiowei; Akpos, Helen Tamunoibi (Research Journal of Economics and Sustainable Development, 2024)
This study investigates the impact of corporate governance mechanisms on the financial performance of listed consumer goods manufacturing firms in Nigeria between 2011 and 2020. The study examines the influence of board size, board independence, board compensation, and board diligence on return on equity. The findings reveal a negative and insignificant correlation between board size and return on equity, whereas board independence has a negative and significant relationship with return on equity. Board compensation, on the other hand, has a positive and significant impact on return on equity, while board diligence has a negative and significant relationship with return on equity. Based on the results, the study concludes that corporate governance mechanisms have a significant impact on the financial performance of listed consumer goods manufacturing firms in Nigeria. This highlights the importance of robust governance practices for improving a firm's long-term sustainability. The study suggests increasing board size, appointing non-executive directors, and ensuring appropriate board compensation and diligence practices to boost financial performance.